X-ray absorption spectroscopy and Eu3+-emission characteristics in GaAs/SnO2 heterostructure - Bueno, Cristina F. [UNESP]; Ramos, Aline Y.; Bailly, Aude; Mossang, Eric; Scalvi, Luis V. A. [UNESP] (Springer, 2020)
X-ray absorption near edge structure (XANES) and extended X-ray absorption fine structure (EXAFS) data are used for investigating heterostructure samples of GaAs/SnO2. XANES data are used for analyzing the local organization around Eu in the heterostructure formed by GaAs and Eu-doped SnO2. The differences between the XANES data for these samples and data obtained for Eu-doped SnO2 thin films, deposited on glass substrate, are assumed as responsible for the differences in the photoluminescence (PL) spectra concerning the Eu3+ emission, since films deposited on glass substrate do not present Eu3+ PL transitions until the annealing temperature is rather high. Eu3+ emission is explored using two different excitation sources: 350 nm from a Kr+ laser (above SnO2 energy bandgap) and 488 nm from an Ar+ laser (below SnO2 bandgap energy). The existence of more organized regions around the Eu3+ site observed for the heterostructure surface may be associated with the Eu3+ luminescent emission. The main and secondary features in the XANES show that there are differences in the average local Eu environment for the SnO2:Eu isolated thin films and heterostructures, being more organized in the latter. Electrical characterization evidences that the portion of the resistivity reduction that corresponds to photo-ionized intrabandgap states is responsible for the persistent photoconductivity phenomenon in the heterostructures.
Keywords: Tin dioxide; Gallium arsenide; Heterostructure; Electro-optical properties